Tri Satya Dan Dasa Darma Sebagai Fondasi Etika Profesi Guru Masa Depan - Safrudin; Ramses Hutagaol; Rejeki; Nauli Tamasari; Debby Indah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2025)
This service program aims to internalize the values of Tri Satya and Dasa Darma Scouts in prospective teacher students. Honesty, responsibility, and care serve as ethical foundations to shape educators with strong character, integrity, and readiness to face contemporary educational challenges.